A comparative study on conversion of industrial coal by-products in low sio2 zeolite of faujasite type (2012)
Colombian industrial coal by-products were evaluated as raw materials in the synthesis at laboratory scale of low SiO2 zeolite of faujasite type using an alkaline fusion step followed by the hydrothermal treatment under various experimental conditions. By fusion with NaOH followed by hydrothermal reaction, coal by-products were converted into zeolite of faujasite type. The process of faujasite formation is discussed.